Integrating Mathematics and Islamic Da'wah in Education: Bridging the Gap Between Science and Religious Values - Ibnu Imam Al Ayyubi; Rima Ayu Handayani; Nayla Damai Vadlina Putri (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
The rapid development of science and digital culture has challenged Islamic da'wah to adopt more contextual and innovative approaches that resonate with younger generations. One emerging strategy is integrating educational disciplines with religious messages. This study aims to analyze the implementation of a contextual approach in developing contemporary Islamic da'wah through mathematics education within Islamic educational settings. Using a qualitative field-based design, data were collected through in-depth interviews with da'wah leaders, mathematics educators, and participants, as well as direct observations and document analysis. The findings reveal that mathematical concepts such as patterns, logic, proportion, and order are contextualized to illustrate Islamic values, including tawhid, ethical reflection, and spiritual awareness. This integration enhances the relevance of da'wah and strengthens the epistemological connection between mathematics and Islamic teachings. The study’s novelty lies in proposing mathematics education as an integrative medium for contextual Islamic da'wah, bridging scientific reasoning and religious values. However, challenges remain, including limited teacher competence and insufficient instructional resources. The study offers practical implications for educators, preachers, and policymakers in developing innovative and sustainable da'wah strategies.